EU GDPR : a pocket guide - Calder, Alan, 1957- (IT Governance Publishing Ltd, 2018)
Now in its second edition, this bestselling book provides a clear understanding of the EU GDPR (General Data Protection Regulation). It has been updated to reflect the latest guidance from the WP29/EDPB (European Data Protection Board) and the ICO (Information Commissioner's Office), as well as offering advice on related laws including the NIS Directive and the forthcoming ePrivacy Regulation.--